Variance Analysis as A Tool for Cost Control on The FIN Fan Cooler Foxtrot Compresor Project at PT Intan Prima Kalorindo - Azis, Azolla Degita; Murtaqi, Isrochmani (The Indonesian Journal of Business Administration, 2014)
Abstract - PT Intan Prima Kalorindo is a company which focused on design, manufacture, installation, and maintenance in Heat Exchanger Industry. Kalorindo is one of the largest Domestic Company of Heat Exchanger in Indonesia with 60 employees and total assets more than Rp 25 Billion in 2012. This company had 13 Projects in 2013. One of their biggest project is Fin Fan Cooler Foxtrot Compressor for Oil and Gas Company with valued $796.500. This project was expected to have profit 60-70% as a source to cover the fixed overhead costs and run business operational. But this project has a gap between budgeted plan and realized until 84%. It will impact to the company that will face several problems, which are debt increase, annual profit decrease, target not achieve, resources become wasted, and inability to pay several expenses.However, to achieve Kalorindo vision, mission, and goals, it is needed to improve their performance and do some strategy to win the competitive advantage. In this research, variance analysis is developed as the synthesis of literature and case study. This model is utilized to analyze the cause from differences between standard and actual project budget through define the cost allocation and behavior. This research shows that this company has unfavorable price and efficiency variance on Foxtrot Compressor Project. The proposed business solution implementation is based on the analysis result, includes KaizenStandard Costing PDCA scheme and schedule planning to have an evaluation for its employeesand departments in Kalorindo, and help them to define their strategy plan as continuous improvement for the future. Keyword: Heat Exhanger, Cost Behavior, Variance Analysis, Kaizen Standard Costing